Current Status and Outlook in the Application of Microalgae in Biodiesel Production and Environmental Protection - Zhang, Xin; Rong, Junfeng; Chen, Hui; He, Chenliu; Wang, Qiang (Frontiers in Energy Research, 2014)
Microalgae have been currently recognized as a group of the most potential feedstocks for biodiesel production due to high productivity potential, efficient biosynthesis of lipids, and less competition with food production. Moreover, utilization of microalgae with environmental purposes (CO2 fixation, NOx, and wastewater treatment) and biorefinery has been reported. However, there are still challenges that need to be addressed to ensure stable large-scale production with positive net energy balance. This review gives an overview of the current status of the application of microalgae in biodiesel production and environmental protection. The practical problems not only facing the microalgae biodiesel production but also associated with microalgae application for environmental pollution control, in particular biological fixation of greenhouse gas (CO2 and NOx) and wastewater treatment are described in detail. Notably, the synergistic combination of various applications (e.g., food, medicine, wastewater treatment, and flue gas treatment) with biodiesel production could enhance the sustainability and economics of the algal biodiesel production system.